Fatores de risco para mucosite oral durante tratamento antineoplásico: estudo observacional e revisão sistemática e metanálise - Martins, Joyce Ohana de Lima (2022)
Introduction: Serious adverse effects such as oral mucositis (OM) can lead to interruption of chemotherapy treatment (CT), reduction of doses and its effectiveness. Objective: To analyze risk factors for OM. Materials and methods: An observational study guided by STROBE was performed with 19,000 OM assessments of patients undergoing chemotherapy for solid tumors at the Instituto do Câncer do Ceará. Clinical data and therapeutic protocols were retrieved for statistical associations. In addition, a systematic review registered in PROSPERO (CRD42021295322) was conducted with search strategies in seven scientific databases and three gray literature bases with the PICOS strategy “patients using antineoplastic chemotherapy (P); use of oral and/or dental hygiene protocols (I); compared to non-use/use of oral and/or dental hygiene protocol placebos (C); reduces the incidence and/or severity of OM (O); controlled clinical trials (S)”. Rob-2 and ROBINS-I risk of bias tools were used, meta-analysis of random effects and quality of evidence analysis (GRADE-pro) were performed. Results: In the observational study, the prevalence of MO was 6.3% (n = 1,195) and the duration of chemotherapy (p<0.001), female sex (p=0.001), adjuvant intent (p=0.008) and the use of carboplatin (p=0.001), cisplatin (p=0.029), docetaxel (p<0.001) and bevacizumab (p=0.026) increased the risk of OM. In head and neck tumors, duration of chemotherapy (p=0.018), BMI>30 (p=0.008), history of radiotherapy (p=0.037) and use of carboplatin (p=0.046) and cyclophosphamide (p=0.010) increased this prevalence. In the systematic review of 3,367 articles evaluated, 25 randomized controlled trials (RCTs) and 14 nonrandomized clinical trials (NRS) were included involving 2,109 and 754 patients, respectively. The risk of bias was low/moderate in RCTs and moderate/severe in RCTs. Mouthwash-based oral hygiene (p<0.001) reduced the severity (Cohen's d = -1.87 [-2.49 to -1.24]) and incidence (RR=0.38, [0.24 to 0.59) of OM and other oral hygiene protocols reduced also the severity (Cohen's d = -0.81 [-1.03 to -0.59]) and incidence (RR=0.64 [0.53-0.70) of MO. GRADE-pro showed moderate levels of evidence. Conclusion: Chemotherapy with cytotoxic drugs and head and neck radiotherapy increase the risk of OM and oral hygiene protocols significantly reduce this incidence.